Celebrating the Prophet's Birthday: a Manifestation of the Character of Cooperation in Islamic Education - Anggita, Sri Ayu; Mahboob, Muhammad Awais; Hussein, Sofian Sauri Bin (Jurnal Pendidikan Agama Islam Indonesia (JPAII), 2024)
Purpose of the study: The aim of this research is to explore and reveal the values of Islamic education in the tradition of celebrating the Prophet's birthday in one of the villages in Indonesia, in several countries such as Iran and Pakistan by integrating qualitative and phenomenological approaches. Methodology: This research uses qualitative methods with a phenomenological approach to explore the values of Islamic education in celebrating the Prophet's birthday in various regions in Indonesia, Iran and Pakistan. Data was collected through interviews, observation and document research, then analyzed through the stages of data reduction, data presentation, verification and drawing conclusions. Main Findings: The research results highlight the differences and similarities in the traditions of the Prophet's birthday in Indonesia, Iran and Pakistan. In Indonesia, celebrations tend to reflect local cultural diversity and interfaith tolerance. In Iran, the Prophet's Birthday tradition has become an integral part of Muslim life with the added element of art and performance. Meanwhile in Pakistan, celebrations involve strong religious and social activities, strengthening the bonds of the Muslim community. Novelty/Originality of this study: The novelty of this research lies in exploring the unique aspects of celebrating the birthday of the Prophet Muhammad SAW in madrasah in Indonesia, Iran and Pakistan. This study explores the values of Islamic education embedded in this tradition, contributing fresh insights into various cultural expressions and spiritual meanings in society.